Tensile behaviour of magnesia carbon refractories - Schmitt, N; Berthaud, Y; Poirier, J (Journal of the European Ceramic Society, 2000)
The determination of the Young's modulus and the tensile strength of heterogeneous refractories are the subjects of this paper. Great differences have been observed for a similar material according to both the usual tests performed and the interpretation proposed to define these properties. The causes of the discrepancies of the Young's modulus under compression and tensile loading are examined in detail. Then, it is shown that (i) the accuracy measurement of the deflexion in the bend test with a particular device and (ii) the integration of the shearing distorsion in the calculation of the deflexion by the classical beam theory, allow for finding the appropriate value of the Young's modulus. The classical definition of the modulus of rupture ( M.O.R.) is also examined. Considering a nonlinear behaviour of the refractory, it is shown by finite element analysis of the beam, that the M.O.R. overestimates the tensile strength.